Genetic Diversity of Bali Cattle in Barru Regency Based on Phenotype Characteristics and Microsatelite DNA Identifier - M. Mansur; A. T. B. Astuti Mahmud; M. I. A. Dagong; L. Rahim; Rr. S.R. A. Bugiwati; S. Baco (Jurnal Ilmu dan Teknologi Peternakan, 2016)
Sapi Bali is one of Indonesia germplasm, which has great potential to be developed as a national meat suppliers. Barru regency, South Sulawesi province is one of the purification center of Bali cattle in Indonesia. This study aimed to determine the genetic characteristics of Bali cattle in Barru regency based on identification of phenotype qualitative (horn shape and color of feathers) and quantitative traits (body size), as well as the identifier of microsatellite DNA diversity, in particular HEL9 and INRA035loci. Bali cattle phenotype characterization was done by identifying the typical qualitative properties owned by Bali cattle, as well as a quantitative trait such as body weight, body length, chest circumference and height. Blood samples were collected from about 80 heads of Bali cattle (35 males and 45 females). Extraction of genomic DNA using a DNA extraction kit (GeneJet Genomic DNA Extraction). PCR technique was then used to amplify DNA in microsatellite HEL9 and INRA035loci. Genetic diversity was calculated based on the frequency of alleles and genotypes, observed heterozygosity (Ho), expectated heterozygosity (He) and the Hardy-Weinberg equilibrium. The results showed that the predominant form of horns in males were silak bajeg while the females were silak manggulgangsa, while the percentage of normal color pattern (typical of Bali cattle) was 92.5% and the color pattern deviates ie. 7.5%. In HEL9 locus, alleles found were A and B with only AB genotype(100%). While at the INRA035 locus,were found three alleles ie. A (0.4813), B (0.50) and C (0.0187), with the most common genotype were AB (0.96). Based on shape horn and feather color, the phenotype characteristic  of Bali cattle in the Barru regency were quite diverse, but the genetic diversity of DNA microsatellite observed quite low with only found two alleles (A and B) at HEL9 and 3 alleles (A, B and C ) at the INRA035 locus.